Potensi Antidiabetes Teh Celup Ekstrak Tinospora crispa (L.) dan Stevia rebaudiana Menggunakan Teknik Co-Processing Granulasi Basah - Alfiatul Khasanah; Nawafila Februyani; Atika Nirmala (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Introduction: Diabetes mellitus is a chronic metabolic disorder requiring practical herbal therapies with controlled physical quality. Tinospora crispa (L.) is known to possess antidiabetic potential through its alkaloid, flavonoid, and terpenoid constituents, while Stevia rebaudiana serves as a natural low-calorie sweetener and may offer additional metabolic benefits. This study aimed to evaluate the physical characteristics and antidiabetic potential of tea bags containing a combination of Tinospora crispa (L.) extract and Stevia rebaudiana powder prepared using wet-granulation co-processing technique. Methods: Three formulations were developed with varying concentrations of Tinospora crispa (L.) extract at 5%, 10%, and 15%. Extraction was performed using an ultrasonic-assisted method with 70% ethanol as solvent. Physical quality evaluation included moisture content, weight uniformity, brewing time, infusion pH, and homogeneity. An exploratory in vivo test was conducted on 15 alloxan-induced Swiss Webster mice (n=3 per group) over 7 days. Statistical analysis employed One-Way ANOVA followed by Tukey HSD test at α=0.05 significance level. Results: The extract yield was 39.07%. All formulations demonstrated homogeneity with uniform fill weight of 2 g per bag. Significant differences among formulations were observed in moisture content (*p*=0.001; η²=0.895), brewing time (*p*=0.006; η²=0.822), and infusion pH (*p*=0.031; η²=0.687). In the in vivo study, the positive control and all formulation groups showed a tendency toward decreasing blood glucose levels, whereas the negative control group exceeded the glucometer detection limit (>500 mg/dL) from day 5 to day 7. The formulation containing 10% extract (F2) demonstrated the largest descriptive reduction from 210.67 to 88.00 mg/dL (58.23%). Conclusion: Variations in Tinospora crispa (L.) extract concentration affected several physical quality parameters; however, no single formulation was superior across all tested parameters. The in vivo findings suggest a tendency toward antidiabetic activity, yet further studies with larger sample sizes, placebo controls, active compound standardization, and safety evaluations are required to confirm efficacy and elucidate the mechanism of action.